Predictors of word reading performance in Filipino and in English among grade school children - Ocampo, Dina (The RAP Journal, 2005)
This paper outlines the two dominant positions that describe literacy development, among second language learners. Given that these viewpoints focus on underlying processes involved in literacy (specifically word reading), a description of the proposed skills that lead to able reading are incorporated into the introduction. The underlying skills were selected so that the interaction between cognitive/linguistic skills and bilingualism/biliteracy could be investigated. Findings suggests that both explanations contribute to the better understanding of Filipino-English word reading skill development among grade school children.